The influences of lecturers on foreign language classroom anxiety - Norliani Norliani; Wulida Makhtuna (Lentera: Jurnal Ilmiah Kependidikan, 2017)
This study is to find out the influences of lecturers’ attitudes on foreign language classroom anxiety (FLCA) levels of students. The study has been carried out at the fifth semester students of English Departement of STKIP PGRI Banjarmsin academic year 2015/2016. The data have been collected by means of questionnaire and interview, designed to measure the FLCA levels. The aim of which is to obtain information about the effects of lecturers’ attitudes on students with different anxiety levels. FLCA tested on three dimensions, communication apprehension, fear of negative evaluation, and test anxiety. It was a five point likert’s scale questionnaire, ranging from strongly agree to strongly disagree. Strongly agree was coded by (5) and strongly disagree was coded by (1). The interview and questionnaire were translated into Bahasa Indonesia to make it easy for students to understand. The result of the study have revealed that, in the classroom the level of anxiety increases by the influence of lecturers.